2008
DOI: 10.1128/cvi.00385-07
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Linked Immunosorbent Assay for Detection of Plasmodium falciparum Histidine-Rich Protein 2 in Blood, Plasma, and Serum

Abstract: Microscopy, the gold standard for the detection and quantification of malaria parasites in blood, is in many aspects deficient for this purpose. The method is poorly reproducible and can be inaccurate because Plasmodium falciparum parasites sequester for a portion of each asexual cycle. Due to these deficiencies, biomarkers such as P. falciparum histidine-rich protein 2 (PfHRP2) are increasingly being used. In this study, we evaluated the use of a commercial PfHRP2 enzyme-linked immunosorbent assay (ELISA) kit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
87
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 28 publications
(44 reference statements)
5
87
1
Order By: Relevance
“…The assay proved to be sensitive at all parasitemia tested as indicated by the linearity of the fitted curve. This differed from results were obtained by Kifude et al,42 who demonstrated that the lower level of quantification; that is, the point at which the analysis is feasible, was 3.19 ng ml À1 , corresponding to an OD of 0.05. Linearity in our assay was obtained at all parasitemia tested and the lower limit of quantification was 2.18 ng ml À1 corresponding to an OD of 0.04.…”
Section: Hrp II Methods Validationcontrasting
confidence: 86%
“…The assay proved to be sensitive at all parasitemia tested as indicated by the linearity of the fitted curve. This differed from results were obtained by Kifude et al,42 who demonstrated that the lower level of quantification; that is, the point at which the analysis is feasible, was 3.19 ng ml À1 , corresponding to an OD of 0.05. Linearity in our assay was obtained at all parasitemia tested and the lower limit of quantification was 2.18 ng ml À1 corresponding to an OD of 0.04.…”
Section: Hrp II Methods Validationcontrasting
confidence: 86%
“…Also, the strong correlations did not appear to be different between lower and higher Ab levels. This is an important observation because prior studies concluded that the significant differences observed between serum and plasma concentrations for certain proteins, such as some cytokines or a plasmodial protein, could have been due in part to the overall low concentrations of these proteins (7,11). Another study that reported significant differences in the detection of microglobulin levels between serum and plasma samples suggested that the differences observed could have been due to a nonspecific effect of heparin or citrate on the microglobulin because they were not observed between serum and EDTA plasma (5).…”
mentioning
confidence: 99%
“…For example, some proteins, such as beta-2-microglobulin or Plasmodium falciparum histidine-rich protein 2, have been detected in significantly lower concentrations in human plasma than in serum (5,11), and while very high and significant correlations between plasma and serum levels were obtained for C-reactive protein or insulin (4,7), no statistically significant correlation was found for cytokines such as interleukin-1␤ (IL-1␤) and tumor necrosis factor alpha (TNF-␣) (7). It is also conceivable that storage of plasma samples, which can lead to precipitation of some proteins due to polymerization of fibrin, could result in Ab levels different from those found in serum.…”
mentioning
confidence: 99%
“…Chronoamperometric measurements (Fig. 3D) performed by the uMED show a linear response for concentrations of PfHRP2 in the clinically relevant range of 0-150 ng/mL (30). In this proof-of-principle experiment, the limit of detection was 20 ng/mL.…”
Section: Resultsmentioning
confidence: 76%